Focus Group Discussion: Eksplorasi Pemanfaatan Virtual Reality bagi Guru Madrasah Tsanawiyah di Bantul - Lestari, Puji; Sulisworo, Dwi (Jurnal Pendidikan Madrasah, 2024)
Technology-based learning, particularly the use of Virtual Reality (VR) in education, has been proven to provide significant benefits for both students and teachers by enhancing conceptual understanding and increasing learning enthusiasm. Research shows that VR not only boosts students' interest and motivation to learn, but also enables them to interact directly and visualize complex concepts such as the digestive system, respiratory system, biodiversity, global warming, the excretory system, the solar system, environmental pollution, and others. However, challenges such as high costs, technology availability, and the need for additional teacher training must be addressed to optimize the use of VR in education. Recommendations for further development include diversifying VR content and features, as well as broader integration into educational curricula. With its potential to transform learning paradigms into more interactive and engaging experiences, VR offers tremendous opportunities for students across various educational levels.